Synthesis, characterization, and antibacterial activity of organotin (IV) complexes with 2-hydroxyacetophenone thiocarbohydrazone - Fasihuddin Badruddin, Ahmad; Dayang NA, Chee; Md. Abu, Affan; MR, Asarud; Norrihan, Sam; MA, Salam; Ahmad, Ismail; SH, Tan (Taylor & Francis Group, 2011)
Six new organotin(IV) complexes were synthesized by direct reaction of RSnCl3 (R = Me, Bu and Ph) or R2SnCl2 (R = Me, Bu and Ph) and 2-hydroxyacetophenone thiocarbohydrazone [H2APTC] under purified nitrogen in the presence of base in 1 : 2 : 1 molar ratio (metal: base: ligand). Complexes 2–7 have been characterized by elemental analyses, molar conductivity, UV-Visible, IR and 1H NMR spectral studies. Complexes 2–7 are non-electrolytes. The molecular structure of [Me2Sn(APTC)] · (C2H5OH) (5) has been determined by X-ray diffraction analysis. The thiocarbohydrazone ligand (1) and 2–7 have been tested for antibacterial activity against Escherichia coli, Staphylococcus aureus, Salmonella typhi and Enterococci aeruginosa.